KALKULATOR SEDERHANA UNTUK TUNANETRA DENGAN OUTPUT SUARA - , HARI PRASETYA NUGRAHA; , Ir. Suyoto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the difficulties in the use of the calculator is common to blind the difficulty of identifying key and the results displayed on the lcd screen. So by adding a button with braille and results of votes, can make it easier for users to use it. This tool has several major components namely, microcontroller ATmega32 as controller, voice IC ISD 25120 as storage media sound and speakers as output. These speakers sound Output expanded feet according figures pressed and also released the results of a calculation is done.